Chinese historiography in comparative perspective - Schneider, Axel (History and theory / Theme issue;, 1996)
Based on papers presented at the international symposium on "Chinese Historiography in Comparative Perspective", held at the Institute of Chinese Studies at Heidelberg University in Mar. 1995.